Bio-functionalisation of polyelectrolyte microcapsules with biotinylated poly (ethylene glycol)- grafted liposomes for application in targeted drug delivery - Gao, Jie (2012)
Progress in chemistry and biotechnology allowed the development of nanoengineered delivery systems that can encapsulate a wide variety of novel therapeutics such as proteins, chemotherapeutics, and nucleic acids. It is always interesting to functionalize the delivery systems to be “intelligent” and multi-functional, such that they can avoid the uptake by macrophages and deliver their payload at a specific position, e.g. target to a pathogen tissue. Polyelectrolyte capsules, made by layer-by-layer (LbL) coating of a sacrificial template followed by dissolution of the template, have been studied intensively as potential drug delivery carriers. LbL